Corporate Control Contests and the Asymmetric Disclosure of Bad News: Evidence from Peer Firm Disclosure Response to Takeover Threat - Chen, Shuping; Miao, Bin; Valentine, Kristen (The Accounting Review, 2022)
ABSTRACT We examine the voluntary disclosure behavior of peer firms of hostile takeover targets. We find that peer firms under control threat use a disclosure strategy that emphasizes bad news: they provide more bad news forecasts, tend to bundle bad news forecasts with earnings announcements, use more negative tone in conference call presentations, and more evenly distribute negative tonal words throughout the presentation to heighten the visibility of bad news. This asymmetric disclosure of bad news is concentrated in firms whose managers have greater incentives to mitigate the control threat—firms with younger CEOs, CEOs with higher total compensation, and firms with weaker anti-takeover provisions. Further tests show that peer firms also manage accruals downward. We contribute to the sparse literature on the impact of corporate control contests on voluntary disclosure by demonstrating that peer firms under control threat emphasize bad news to preempt control threat. JEL Classifications: G14; G32; M4; M41.